The Influence of Cultural Factors, Social Factors, and Personal Factors against Customer Purchase Decisions in Using Wedding Services Organizer in Surabaya - Rachmat Santosa (Universitas Ciputra Surabaya, 2021)
Wedding organizer services are needed and sought to help resolve problems owned by the prospective bride and groom. This study aims to examine and analyze cultural factors, social factors and personal factors as variables that influence customer purchasing decisions in using wedding organizer services in Surabaya. This type of research is quantitative, the sampling technique used is purposive sampling in the form of a number questionnaire where the population is unknown. By using the criteria of respondents who are married and the age of marriage that runs a maximum of 5 (five) years and uses the services of a wedding organizer. A sample of 97 respondents was obtained from the calculation of the formula unknown population. The results obtained that cultural factors have a positive and significant influence on purchasing decisions. But social factors and personal factors partially do not significantly influence the purchase decision. So business managers must improve their outlook on finding clients and improving the quality of services so that customers are easier to choose these services.